Hegemoni kerajaan Gowa dan Perang Makassar - -, Fadli (Rihlah: Jurnal Sejarah dan Kebudayaan, 2022)
The Makassar war is one of the major wars that occurred in the archipelago, so it is important to study it. Seeing that the impact was large enough for a change in the life of the Makassar people at that time, thus making the Gowa-Tallo kingdom have to accept defeat and compensate for all war losses, and must be bow to the Dutch East Indies government. This study is a historical study with the stages of heuristics, criticism, interpretation, and historiography. Based on the results of the initial study, information was obtained regarding the background of the Makassar war, the course of the Makassar war until the collapse of the Gowa-Tallo kingdom as a sign of the end of the Makassar war. However, the resistance was continued by the kings of the vassal kingdoms of Makassar, so that some people had to choose between participating in the rebellion or submitting to the Dutch East Indies government. Finally, at the end of the 17th century the dissidents were conquered and the government succeeded in establishing a central government centered on the Fort Roterdam. This is what researchers will study in order to be able to provide results related to socio-economic life after the Makassar war.